Two new butterfly records for Peru: Orophila cardases cardases and Pedaliodes garlaczi (Lepidoptera: Nymphalidae) - Cerdeña, José Alfredo (2014)
We report to Peru, for the first time, two butterfly species, Orophila cardases cardases (Hewitson, 1869) and Pedaliodes garlaczi Pyrcz & Cerdeña, 2013, based on specimens collected in the Tabaconas-Namballe National Sanctuary and neighboring areas.